Does the spillage of petroleum products in Anopheles breeding sites have an impact on the pyrethroid resistance? - Djouaka, R.F.; Bakare, A.A.; Bankole, H.S.; Doannio, J.M.C.; Coulibaly, O.N.; Kossou, H.; Tamo, Manuele; Basene, H.I.; Popoola, K..K.; Akogbeto, M.C. (Springer, 2007)
Background